Acceptance for Human Papilloma virus vaccines, experience at tertiary care centre of northern india: a hospital-based survey - Verma, Manju Lata; Singh, Uma; Rai, Prachi; Qureshi, Sabuhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Acceptance of HPV vaccine is varying widely worldwide in range of 10-70%. For increasing the acceptability for HPV vaccine, finding the obstacles and catering them diligently is required. The aim of the study was to find out acceptability rate for HPV vaccine in northern India and various obstacles and facilitators affecting acceptance of HPV vaccine. Methods: A questionnaire based descriptive study was done in the Department of Obstetrics and Gynecology of King George Medical University, Lucknow, Uttar Pradesh, India from June 2016 to June 2017. Questionnaire was filled by doctor after taking face to face interview of individuals. Ethical approval was obtained from the Institutional Ethical Committee of the KGMU, Lucknow, Uttar Pradesh, India. (1689/Ethics/R cell/17) acceptability rate and various facilitators and obstacles for HPV vaccine were studied. For continuous variables mean with standard deviation was used. For categorical variables frequencies and percentages were used. IBM SPSS statistics applied. Results: A total of 302 cases were face to face interviewed, amongst which, 70 cases (23%) showed acceptability and 232 did not accept the vaccine. The most common obstacles were lack of knowledge and high monetary cost being the cause of nonacceptance in 48.3% and 33.6% of cases respectively. Conclusions: Higher level of awareness and knowledge about HPV vaccine and inclusion in government immunization programmed may increase acceptability.